Thanatological perspectives in geriatrics and gerontopsychiatry - Greš Alen; Staver Dijana; Šakić Branislav; Radovančević Ljubomir (Scripta Medica, 2023)
Thanatology is the science of death in relation to aging and old age. The concept of death and dying is presented in many works and is the subject of many scientific and professional research. Death and dying do not have their proper place in social understanding and are increasingly being ignored and suppressed. Despite modern medical discoveries and achievements, death still eludes human control. People often avoid talking about death, thinking that death happens to someone else. They consider it as an inevitable reality for some upcoming future.